A two-dimensional DJ-type perovskite solar cell and its preparation method

By doping compounds formed by ammonium salts and carboxylic acids in the perovskite precursor solution, the crystallization kinetics and orientation of two-dimensional perovskites are regulated, and recrystallization is promoted through thermal annealing, the problem of low photoelectric conversion efficiency and stability of two-dimensional perovskite solar cells is solved, and higher photoelectric conversion efficiency and stability are achieved.

CN117881202BActive Publication Date: 2025-04-18GUANGDONG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311653742.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-05
Publication Date
2025-04-18
Estimated Expiration
2043-12-05

AI Technical Summary

Technical Problem

The photoelectric conversion efficiency and stability of existing two-dimensional perovskite solar cells are low, mainly because long chain large volumes of two-dimensional organic spacer materials hinder the transmission of carriers in the vertical direction.

Method used

The ionic compound of butadylammonium diacetate formed by doping ammonium salts and carboxylic acids into the perovskite precursor solution as an organic spacer layer regulates the crystallization kinetics and crystal orientation of the two-dimensional perovskite material, and promotes the recrystallization and grain growth of perovskites through thermal annealing process.

Benefits of technology

The photoelectric conversion efficiency and stability of two-dimensional perovskite solar cells are significantly improved, the carrier transmission in the vertical direction is improved, and non-radiative recombination is effectively suppressed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117881202B_ABST
    Figure CN117881202B_ABST
Patent Text Reader

Abstract

The present invention relates to a two-dimensional DJ type perovskite solar cell, wherein a dibutyl diammonium diacetate ion type compound formed by an ammonium salt and a carboxylic acid is doped in the perovskite precursor solution. The present invention forms an intermediate phase by introducing carboxylate ions into the perovskite system through the strong interaction between the carboxylate ions and the lead ions. In the perovskite film forming process, the rate at which the intermediate phase releases lead iodide during the formation of the perovskite film is slowed down, thereby greatly reducing the crystallization rate and increasing the grain size, thereby enhancing the crystallinity of the perovskite crystal and effectively inhibiting non-radiative recombination. The presence of the intermediate phase can improve the 2D perovskite grain boundary orientation, thereby enhancing the vertical transmission of carriers and enhancing the performance of the solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photovoltaic materials and devices, and specifically relates to a two-dimensional DJ-type perovskite solar cell and a preparation method thereof. Background Art

[0002] At present, the highest power conversion efficiency of a single perovskite solar cell (26.1%) is comparable to that of commercial silicon solar cells. Among the functional layer materials of perovskite solar cells, the perovskite light-absorbing layer has attracted much attention as a key component of perovskite solar cells due to its high solar extinction coefficient, adjustable bandgap width, long carrier diffusion length and superior carrier mobility.

[0003] Among the various strategies to improve the stability of perovskite solar cells, introducing low-dimensional halide perovskites into three-dimensional perovskite materials to enhance the stability of the cells in natural environmental conditions (e.g., moisture, heat, and light), or reducing the dimensionality of three-dimensional perovskites to low-dimensional perovskites (usually two-dimensional) as the light-absorbing layer of perovskite solar cells through dimensionality reduction methods are two strategies that are currently more feasible and effective.

[0004] Adding long-chain and bulky two-dimensional organic spacer materials, such as ammonium butyl or diammonium butyl, to form a two-dimensional layered perovskite phase is an effective way to improve the chemical stability of perovskites. Although these materials appear to have better chemical stability under various environmental conditions, their photovoltaic performance is generally inferior to that of perovskite solar cells prepared based on three-dimensional perovskite materials, mainly because the introduction of long-chain and bulky two-dimensional organic spacer materials hinders the transport of carriers in the vertical direction. Therefore, by designing and introducing new organic spacer materials to regulate the crystallization kinetics and crystallization orientation of two-dimensional perovskite materials, it has a significant effect on improving the photoelectric conversion efficiency and stability of two-dimensional perovskite solar cells, which is of great significance to promote the further industrialization of perovskite solar cells.

[0005] In summary, there is an urgent need to develop a new technical solution to solve the defects in the existing technology and further improve the photoelectric conversion efficiency of perovskite photovoltaic devices. Summary of the invention

[0006] Based on this, in order to improve the photoelectric conversion efficiency and stability of two-dimensional perovskite solar cells, the present invention provides a two-dimensional DJ-type perovskite solar cell constructed by doping ammonium salts and carboxylic acids in a perovskite precursor solution and a preparation method thereof. The two-dimensional DJ-type perovskite solar cell introduces dibutyl ammonium diacetate ion-type compounds as the source of organic spacer cations. The strong interaction between carboxylate ions and lead ions forms an intermediate phase. In the process of perovskite film formation, first, the presence of carboxylate ions slows down the release of lead iodide from the intermediate phase, thereby greatly reducing the crystallization rate and increasing the grain size. In addition, the ion bond between ammonium ions and carboxylate ions is broken, which can quickly release ammonium ions, allowing ammonium ions to participate in the construction process of DJ-type perovskite, forming a quantum well structure unique to two-dimensional perovskite; after the intermediate phase is converted into a perovskite phase, carboxylate ions and excess formamidine (FA) ions are evaporated in the form of gas in the thermal annealing process, prompting the perovskite to recrystallize and grow with grains, thereby enhancing the crystallinity of the perovskite crystal and effectively inhibiting non-radiative recombination. The effective removal of carboxylate ions and excess FA ions in the thermal annealing process can prevent these non-optically active substances from capturing electrons and holes in the film, affecting the performance of the perovskite solar cell.

[0007] One object of the present invention is to provide a two-dimensional DJ-type perovskite solar cell, in which an ionic compound formed by a large volume of diammonium salt and a carboxylate is used as a reactant in a perovskite layer precursor solution; the two-dimensional DJ-type perovskite layer formed thereby is doped with a large volume of diammonium salt as an organic spacer layer, thereby improving the stability of the perovskite layer and the corresponding solar cell device.

[0008] Furthermore, the perovskite layer contains perovskite, and the component structure of the perovskite is A'A n-1 B n X 3n+1 , wherein the A'-site ion is an organic diammonium cation provided by a diacetate diammonium ion compound formed by a bulky diammonium salt and a carboxylate, the A-site ion is an organic / inorganic cation, the B-site ion is a metal cation, and the X-site ion is a halogen anion.

[0009] Furthermore, the molar ratio of the ammonium salt to the carboxylic acid is 1:1-1:10.

[0010] Further, the ammonium salt is selected from 1,3-propanediammonium (PDA), 1,4-butyldiammonium (BDA), 1,5-pentanediammonium (PeDA), 1,6-hexanediammonium (HDA), 1,8-octandiammonium (ODA), 1,4-cyclohexanediammonium (CHDA), 1,4-cyclohexanedimethylammonium (CHDMA), p-phenylenediammonium (PPDA), and p-phenylenediammonium (PPDMA).

[0011] Furthermore, the carboxylic acid is selected from formic acid, acetic acid, propionic acid and butyric acid.

[0012] Furthermore, n is selected from 4-5.

[0013] Another object of the present invention is to provide a method for preparing the above-mentioned two-dimensional DJ-type perovskite solar cell, which comprises the following steps:

[0014] S1, placing a dibutyl diammonium acetate ion compound formed by an ammonium salt and a carboxylate, a lead halide and a formamidine halide in a solvent and stirring to obtain a perovskite precursor solution;

[0015] S2, spin coating the perovskite precursor solution onto a glass substrate, and adding an anti-solvent after a certain period of spin coating;

[0016] S3, thermal annealing treatment, reaction to generate DJ-type perovskite, and evaporate low-boiling point substances (such as residual carboxylate ions and excess FA ions) to obtain the perovskite layer.

[0017] The ammonium carboxylate salt interacts with the lead ions in the precursor solution through coordination, or is free in the solution.

[0018] The above-mentioned lead halide and formamidine halide can be selected from lead iodide or lead bromide, and formamidine iodide or formamidine bromide. We unexpectedly found that higher quality perovskites can be obtained by partially replacing lead iodide with lead bromide and partially replacing formamidine iodide with formamidine bromide. Since the electronegativity of bromide ions is higher than that of iodide ions, the lead-bromine bond has a larger bond energy and a shorter bond length than the lead-iodine bond. From a thermodynamic point of view, this leads to changes in the formation energy of the δ phase and the α phase after the introduction of bromide ions, resulting in significant changes in the nucleation and nucleation growth trends of perovskite. Moreover, bromide ions are preferentially incorporated into corner-sharing sites, promoting the preferential growth of halide perovskite crystal faces, resulting in changes in the crystal orientation of halide perovskites. Finally, the incorporation of bromide ions can promote the formation of the α phase during spin coating and accelerate the transformation of the δ phase to the α phase during annealing.

[0019] Furthermore, the anti-solvent is selected from chlorobenzene solvents, toluene solvents or ester solvents, or derivatives of the above solvents. The anti-solvent can extract the residual solvent that has not been completely volatilized in the early stage of spin coating, so as to make the solute supersaturated and promote crystallization.

[0020] Furthermore, the solvent is selected from one or more of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO).

[0021] The crystallization process of two-dimensional halide perovskites is particularly sensitive to solvents. Solvents have different polarities, viscosities, boiling points, and coordination abilities. These properties lead to large differences in solvent evaporation and the formation of intermediates, which directly affect the crystallization kinetics of two-dimensional halide perovskites. During the crystallization of two-dimensional halide perovskite films, a large amount of nucleation makes the crystallization process difficult to control, resulting in random orientation. Both DMF and DMSO can form intermediates with perovskite precursors. The formation of intermediates induces the aggregation of perovskite precursor solutions, acting as nucleation sites, greatly reducing the density of crystal nuclei in the solution, which is conducive to the formation of films with suitable orientation and large grains.

[0022] Furthermore, the annealing temperature is 100-150° C., and the annealing time is 5-30 min.

[0023] The structure of the perovskite battery prepared by the present invention can be, but is not limited to, substrate / hole transport layer / perovskite layer / electron transport layer / hole blocking layer / metal electrode layer.

[0024] In a specific embodiment of the present invention, the substrate can be ITO, the hole transport layer can be poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), the electron transport layer can be PCBM, the hole blocking layer can be 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline (BCP), and the metal electrode layer can be Ag.

[0025] In a specific embodiment of the present invention, the substrate needs to be subjected to specific treatment before use, which specifically includes the following steps: multiple cleaning with washing liquid, deionized water, acetone, and ethanol and drying; and plasma surface treatment.

[0026] In a specific embodiment of the present invention, the preparation of the hole transport layer includes the following steps: dissolving 5 mg of PTAA in 1 ml of chlorobenzene (CB), stirring at 70°C for 8 hours to obtain a hole transport layer material; spin coating the hole transport layer material onto a substrate and annealing; the specific conditions for spin coating are spin coating at 5000 rpm for 30 seconds; the specific conditions for annealing are annealing at 120°C for 5 minutes.

[0027] In a specific embodiment of the present invention, the preparation process of the perovskite active layer is the preparation process of the above-mentioned perovskite material, wherein the substrate is a hole transport layer; the specific conditions of spin coating are: spin coating at 5000 rpm for 30 seconds, and adding anti-solvent CB; the specific conditions of annealing are annealing at 150°C for 10 minutes.

[0028] In a specific embodiment of the present invention, the preparation of the electron transport layer includes the following steps: dissolving 20 mg of PCBM in 1 ml of CB, stirring at 70° C. for 8 hours to obtain an electron transport layer material; spin coating the electron transport layer material onto the perovskite active layer and annealing; the specific conditions for spin coating are spin coating at 2000 rpm for 30 seconds; the specific conditions for annealing are annealing at 70° C. for 10 minutes.

[0029] In a specific embodiment of the present invention, the preparation of the hole blocking layer includes the following steps: dissolving 2 mg of BCP in 1 ml of isopropyl alcohol (IPA), stirring at 70° C. for 8 hours to obtain a hole blocking layer material; spin coating the hole blocking layer material onto the electron transport layer; the specific conditions of the spin coating are spin coating at 2000 rpm for 30 seconds.

[0030] In a specific embodiment of the present invention, the preparation process of the metal electrode layer may include the following steps: placing a substrate that has been coated with a hole transport layer, a perovskite active layer, an electron transport layer, and a hole blocking layer in sequence into a mask, with the side without the coating layer facing up; placing the mask into a vapor deposition chamber; placing metal Ag particles into a molybdenum evaporation boat, heating them with electricity to evaporate them, so that Ag is slowly deposited on the hole blocking layer.

[0031] The beneficial effects of the present invention are:

[0032] The present invention introduces carboxylate ions into a perovskite precursor solution, and forms an intermediate phase through the strong interaction between carboxylate ions and lead ions. In the perovskite film forming process, first, the presence of carboxylate ions slows down the release rate of lead iodide from the intermediate phase, thereby greatly reducing the crystallization rate and increasing the grain size. In addition, the ionic bond between ammonium ions and carboxylate ions is broken, which can quickly release ammonium ions, so that ammonium ions can participate in the construction process of perovskite, forming a quantum well structure unique to two-dimensional perovskite; after the intermediate phase is converted into a perovskite phase, the carboxylate ions and excess FA ions are evaporated in the form of gas under thermal annealing, prompting the perovskite to recrystallize and grow with grains, thereby enhancing the crystallinity of the perovskite crystal and effectively inhibiting non-radiative recombination. At the same time, the presence of the intermediate phase can improve the 2D perovskite grain boundary orientation, thereby enhancing the transmission of carriers in the vertical direction, and finally obtaining a perovskite solar cell with enhanced device performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 Schematic diagram of the structure of a perovskite solar cell composed of the perovskite material prepared in Example 1 of the present invention.

[0034] Figure 2 It is a JV diagram of a perovskite solar cell composed of the perovskite materials prepared in Comparative Example 1 and Example 1 of the present invention.

[0035] Figure 3 EQE diagram of the perovskite solar cell composed of the perovskite materials prepared in Comparative Example 1 and Example 1 of the present invention.

[0036] Figure 4 PL spectra of the perovskite materials prepared in Comparative Example 1 and Example 1 of the present invention.

[0037] Figure 5 The UV-visible absorption spectra of the perovskite materials prepared in Comparative Example 1 and Example 1 of the present invention.

[0038] Figure 6 These are SEM images of the perovskite materials prepared in Comparative Example 1 and Example 1 of the present invention. DETAILED DESCRIPTION

[0039] In order to more clearly illustrate the technical solution of the present invention, the following examples are listed. Unless otherwise stated, the raw materials, reactions and post-treatment methods shown in the examples are common raw materials on the market and technical methods well known to those skilled in the art.

[0040] The words "preferred", "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that can provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.

[0041] It should be understood that, except in any operating examples, or where otherwise indicated, all numbers indicating, for example, the amounts of ingredients used in the specification and claims should be understood to be modified in all cases by the term "about". Therefore, unless indicated to the contrary, the numerical parameters set forth in the following specification and the appended claims are approximate values ​​that vary depending on the desired properties to be obtained by the present invention.

[0042] In a specific embodiment of the present invention, the preparation of the hole transport layer includes the following steps: dissolving 5 mg PTAA in 1 ml CB, stirring at 70° C. for 8 hours to obtain a hole transport layer material; spin coating the hole transport layer material onto a substrate and annealing; the specific conditions for spin coating are spin coating at 5000 rpm for 30 seconds; the specific conditions for annealing are annealing at 120° C. for 5 minutes.

[0043] In a specific embodiment of the present invention, the preparation process of the perovskite active layer is the preparation process of the above-mentioned perovskite material, wherein the substrate is a hole transport layer; the specific conditions of spin coating are: spin coating at 5000 rpm for 30 seconds, and adding anti-solvent CB; the specific conditions of annealing are annealing at 150°C for 10 minutes.

[0044] In a specific embodiment of the present invention, the preparation of the electron transport layer includes the following steps: dissolving 20 mg of PCBM in 1 ml of CB, stirring at 70° C. for 8 hours to obtain an electron transport layer material; spin coating the electron transport layer material onto the perovskite active layer and annealing; the specific conditions for spin coating are spin coating at 2000 rpm for 30 seconds; the specific conditions for annealing are annealing at 70° C. for 10 minutes.

[0045] In a specific embodiment of the present invention, the preparation of the hole blocking layer includes the following steps: dissolving 2 mg BCP in 1 ml IPA and stirring at 70° C. for 8 hours to obtain a hole blocking layer material; spin coating the hole blocking layer material onto the electron transport layer; the specific conditions of the spin coating are spin coating at 2000 rpm for 30 seconds.

[0046] In a specific embodiment of the present invention, the preparation process of the metal electrode layer may include the following steps: placing a substrate that has been coated with a hole transport layer, a perovskite active layer, an electron transport layer, and a hole blocking layer in sequence into a mask, with the side without the coating layer facing up; placing the mask into a vapor deposition chamber; placing metal Ag particles into a molybdenum evaporation boat, heating them with electricity to evaporate them, so that Ag is slowly deposited on the hole blocking layer.

[0047] The preparation method of the diacetic acid butyl diammonium ion compound of the present invention is as follows: add 1,4-diaminobutane (88.15 g, 1.0 mol) into a 1L three-necked flask, add 200 ml of methanol, stir and cool to (0-20)°C, slowly drop glacial acetic acid (60.05 g, 1.0 mol) until the dropwise addition is complete, and stir at room temperature for 2 hours.

[0048] Then, concentrate under negative pressure at 60°C for 1 hour, heat to 80°C and concentrate for 1 hour, filter and remove mechanical impurities to obtain 138g of product with a purity of more than 99% and a yield of about 95%.

[0049] Example 1

[0050] A two-dimensional DJ-type perovskite solar cell, whose structure is substrate ITO (70nm) / hole transport layer PTAA (25nm) / (BDA)(FA) 3 Pb 4 (I 0.9 Br 0.1 ) 13(250nm) / electron transport layer PCBM (35nm) / hole blocking layer BCP (8nm) / metal electrode layer Ag (90nm).

[0051] The method for preparing the above-mentioned two-dimensional DJ-type perovskite solar cell comprises the following steps:

[0052] S1, (BDA)(FA) 3 Pb 4 (I 0.9 Br 0.1 ) 13 Preparation: dibutyl diammonium diacetate ionic compound, lead iodide, lead bromide and formamidine iodide powder (1:3.35:0.65:5, m / m / m / m) are placed in a mixed solvent of DMF and DMSO (10:1, v / v) and stirred until uniform to obtain a perovskite precursor solution, wherein the concentration of the solution is 0.8 mmol / mL (measured in lead ion concentration);

[0053] S2, spin coating the perovskite precursor solution onto the ITO glass substrate, and adding 100 μl of anti-solvent CB;

[0054] S3, annealing at 150° C. for 10 min to evaporate low-boiling-point substances and obtain the perovskite layer of a specified thickness.

[0055] The other layers of the two-dimensional DJ-type perovskite solar cell are conventionally spin-coated according to technical means well known to those skilled in the art, and finally a two-dimensional DJ-type perovskite solar cell is obtained.

[0056] In the obtained perovskite layer, A'A n-1 B n X 3n+1 The n value is 4, that is, the number of inorganic layers between adjacent organic spacer layers of the two-dimensional DJ halide perovskite is 4. Figure 1 Schematic diagram of the structure of a perovskite solar cell composed of the perovskite material prepared in Example 1 of the present invention.

[0057] Example 2

[0058] A two-dimensional DJ-type perovskite solar cell, whose structure is substrate ITO (70nm) / hole transport layer PTAA (25nm) / (BDA)(FA) 4 Pb 5 (I 0.9 Br 0.1 ) 16 (250nm) / electron transport layer PCBM (35nm) / hole blocking layer BCP (8nm) / metal electrode layer Ag (90nm).

[0059] The method for preparing the above-mentioned two-dimensional DJ-type perovskite solar cell comprises the following steps:

[0060] S1, (BDA)(FA) 4 Pb 5 (I 0.9 Br 0.1 ) 16 Preparation: dibutyl diammonium diacetate ionic compound, lead iodide, lead bromide and formamidine iodide powder (1:4.2:0.8:6, m / m / m / m) are placed in a mixed solvent of DMF and DMSO (10:1, v / v) and stirred until uniform to obtain a perovskite precursor solution, wherein the concentration of the solution is 0.8 mmol / mL (measured in lead ion concentration);

[0061] S2, spin coating the perovskite precursor solution onto the ITO glass substrate, and adding 100 μl of anti-solvent CB;

[0062] S3, annealing at 150° C. for 10 min to evaporate low-boiling-point substances and obtain the perovskite layer of a specified thickness.

[0063] The other layers of the two-dimensional DJ-type perovskite solar cell are conventionally spin-coated according to technical means well known to those skilled in the art, and finally a two-dimensional DJ-type perovskite solar cell is obtained.

[0064] In the obtained perovskite layer, A'A n-1 B n X 3n+1 The n value is 5, that is, the number of inorganic layers between adjacent organic spacer layers of the two-dimensional DJ halide perovskite is 5.

[0065] Example 3

[0066] A two-dimensional DJ-type perovskite solar cell, whose structure is substrate ITO (70nm) / hole transport layer PTAA (25nm) / (BDA)(FA) 3 Pb 4 (I 0.9 Br 0.1 ) 13 (250nm) / electron transport layer PCBM (35nm) / hole blocking layer BCP (8nm) / metal electrode layer Ag (90nm).

[0067] The method for preparing the above-mentioned two-dimensional DJ-type perovskite solar cell comprises the following steps:

[0068] S1, (BDA)(FA) 3 Pb 4 (I 0.9 Br 0.1 )13 Preparation: dibutyl diammonium diacetate ionic compound, lead iodide, formamidine bromide and formamidine iodide powder (1:4:1.3:3.7, m / m / m / m) are placed in a mixed solvent of DMF and DMSO (10:1, v / v) and stirred until uniform to obtain a perovskite precursor solution, wherein the concentration of the solution is 0.8 mmol / mL (measured in lead ion concentration);

[0069] S2, spin coating the perovskite precursor solution onto the ITO glass substrate, and adding 100 μl of anti-solvent CB;

[0070] S3, annealing at 150° C. for 10 min to evaporate low-boiling-point substances and obtain the perovskite layer of a specified thickness.

[0071] The other layers of the two-dimensional DJ-type perovskite solar cell are conventionally spin-coated according to technical means well known to those skilled in the art, and finally a two-dimensional DJ-type perovskite solar cell is obtained.

[0072] In the obtained perovskite layer, A'A n-1 B n X 3n+1 The n value is 4, that is, the number of inorganic layers between adjacent organic spacer layers of the two-dimensional DJ halide perovskite is 4.

[0073] Comparative Example 1

[0074] The structure and preparation method of Comparative Example 1 are the same as those of Example 1, except that in step S1, the diacetic acid butyl diammonium ion compound is replaced by 1,4-butylene diamine hydroiodide in an equimolar amount.

[0075] Comparative Example 2

[0076] The structure and preparation method of Comparative Example 2 are the same as those of Example 1, with the only difference being that in step S1, the diacetate butylenediammonium ion compound is partially replaced by dibutylenediamine hydroiodide, wherein the molar ratio of the diacetate butylenediammonium ion compound to 1,4-dibutylenediamine hydroiodide is 1:9.

[0077] Other comparison ratios

[0078] The replacement situations of other comparative examples 3-14 are shown in the following Table 1.

[0079] Table 1 Material replacement of comparative examples 3-14

[0080]

[0081]

[0082] Test Case

[0083] The performance tests of the perovskite materials and the corresponding batteries were carried out on the above-mentioned Examples 1-3 and Comparative Examples 1-14, and the obtained data are shown in Table 2.

[0084] Table 2 Related perovskite solar cell data

[0085]

[0086]

[0087] in,

[0088] Figure 2 The JV diagram of the perovskite solar cell composed of the perovskite materials prepared in Comparative Example 1 and Example 1 of the present invention. Figure 2 It can be seen that the perovskite film obtained in Example 1 of the present invention has a higher short-circuit current and fill factor, and therefore has a higher photoelectric conversion efficiency than the perovskite in Comparative Example 1.

[0089] Figure 3 EQE diagram of the perovskite solar cell composed of the perovskite materials prepared by comparative example 1 and example 1 of the present invention. In the EQE diagram of the perovskite solar cell provided by the present invention, the light response intensity of the perovskite film can be represented by the external quantum efficiency. Figure 3 It can be seen that the perovskite film obtained in Example 1 of the present invention has a higher external quantum efficiency in the entire band, which indicates that the perovskite film in Example 1 has a higher light response intensity and can efficiently convert incident photons into electrons.

[0090] Figure 4 PL spectra of the perovskite materials prepared in Comparative Example 1 and Example 1 of the present invention. In the PL spectra of the perovskite film provided by the present invention, the recombination of carriers in the perovskite film can be indirectly represented by the photoluminescence intensity. Figure 4 It can be seen that the perovskite film obtained in Example 1 of the present invention has a higher photoluminescence intensity, indicating that the non-radiative recombination inside the perovskite film in Example 1 is effectively suppressed.

[0091] Figure 5 The UV-visible absorption spectra of the perovskite materials prepared in Comparative Example 1 and Example 1 of the present invention are shown in FIG. Figure 5 It can be seen that the perovskite film obtained in Example 1 of the present invention has a stronger absorbance in the full band range.

[0092] Figure 6 The SEM images of the perovskite materials prepared in Comparative Example 1 and Example 1 of the present invention are shown in FIG. Figure 6 It can be seen that the perovskite film obtained in Example 1 of the present invention has larger grains and a smoother surface.

[0093] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0094] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A two-dimensional DJ-type perovskite solar cell, characterized in that: The perovskite precursor solution of the two-dimensional DJ-type perovskite solar cell is doped with an ionic compound formed by an ammonium salt and a carboxylic acid; The perovskite layer contains perovskite, and the component structure of the perovskite is A'A n-1 B n X 3n+1 , wherein the A'-site ion is an organic diammonium cation provided by the bulk spacer material, the A-site ion is an organic / inorganic cation, the B-site ion is a metal cation, and the X-site ion is a halogen anion; in, n is selected from 4 to 5; The method for preparing the two-dimensional DJ-type perovskite solar cell comprises the following steps: S1, placing a dibutyl diammonium acetate ion compound formed by an ammonium salt and a carboxylate, a lead halide and a formamidine halide in a solvent and stirring to obtain a perovskite precursor solution; S2, spin coating the perovskite precursor solution onto a glass substrate and adding an anti-solvent; S3, thermal annealing treatment, reaction to generate DJ-type perovskite, and evaporate low-boiling point substances to obtain the perovskite layer.

2. The two-dimensional DJ-type perovskite solar cell according to claim 1, characterized in that: The molar ratio of the ammonium salt to the carboxylic acid is 1:1-1:

10.

3. The two-dimensional DJ-type perovskite solar cell according to claim 1, characterized in that: The ammonium salt is selected from 1,3-propanediammonium, 1,4-butyldiammonium, 1,5-pentanediammonium, 1,6-hexanediammonium, 1,8-octandiammonium, 1,4-cyclohexanediammonium, 1,4-cyclohexanedimethylammonium, p-phenylenediammonium, and p-phenylenediammonium.

4. The two-dimensional DJ-type perovskite solar cell according to claim 1, characterized in that: The carboxylic acid is selected from formic acid, acetic acid, propionic acid and butyric acid.

5. The two-dimensional DJ-type perovskite solar cell according to claim 1, characterized in that: The anti-solvent is selected from chlorobenzene solvents, toluene solvents or ester solvents, or derivatives of the above solvents.

6. The two-dimensional DJ-type perovskite solar cell according to claim 1, characterized in that: The solvent is selected from one or more of N,N-dimethylformamide and dimethyl sulfoxide.

7. The two-dimensional DJ-type perovskite solar cell according to claim 1, characterized in that: The annealing temperature is 100-150° C., and the annealing time is 5-30 min.

Citation Information

Patent Citations

  • Method for preparing perovskite solar cell by using anti-solvent containing ammonium acetate

    CN114188487A

  • Perovskite thin film, preparation method thereof and perovskite photoelectric device

    CN115835744A